Continuous Security on AWS (The DevSecOps on AWS Series) - Duvall, Paul (Addison-Wesley Professional, 2021)
Almost 4 Hours of Video Instruction Create a continuous security posture by defining all your AWS security and compliance as code, and run in a continuous delivery workflow with every change using services and tools such as AWS CloudFormation, AWS CodePipeline, and many others. Overview In this course, you will learn how to use AWS services, which provide the ability to create an end-to-end continuous security solution. These services include AWS CloudFormation, AWS CodePipeline, Amazon EventBridge, AWS Lambda, AWS Step Functions, AWS Organizations, AWS Security Hub, Amazon GuardDuty, AWS Config Rules, Amazon Inspector, AWS Secrets Manager, Amazon VPC, Amazon Macie, and AWS Audit Manager--among many others. You will learn how to use a combination of these services to apply key design principles for security and build continuous security solutions within your software systems. Throughout the course, you will see working examples of how to automate security using AWS services. About the Instructor Paul Duvall is a founder and former CTO of Stelligent--a Premier Consulting Partner with the DevOps and Security Competencies. He holds multiple AWS certifications including AWS Certified Security - Specialty. He has architected, implemented, and managed software and systems solutions for over 20 years. He is principal author of Continuous Integration: Improving Software Quality and Reducing Risk (Addison-Wesley, 2007), a 2008 Jolt Award winner. He is also the author of many other publications, including the videos Continuous Compliance on AWS and Continuous Encryption on AWS, and Continuous Security on AWS, which are part of Addison-Wesley's DevSecOps on AWS Series. He hosted the "DevOps on AWS Radio" podcast for over three years. He enjoys blogging and speaking on all topics related to DevSecOps, Serverless, and AWS. You can find his blog posts and other content at paulduvall.io . Skill Level Intermediate to Advanced Learn How To Apply key design principles for security Apply event-based design patterns for security Utilize AWS Developer Tools for DevSecOps Use AWS CodePipeline and AWS CloudFormation to model continuous security workflows Define your AWS Organizations as code using org-formation Automate detective controls using AWS CloudFormation, AWS Security Hub, AWS Config Rules, and Amazon Inspector Protect network and host-level boundaries with Amazon VPC Perform data classification using AWS CloudFormation and Amazon Macie Cre ...